2012
DOI: 10.4209/aaqr.2012.07.0163
|View full text |Cite
|
Sign up to set email alerts
|

A Prognostic Approach Based on Fuzzy-Logic Methodology to Forecast PM10 Levels in Khaldiya Residential Area, Kuwait

Abstract: A prognostic approach is proposed based on a fuzzy-logic model to estimate suspended dust concentrations, related to PM 10 , in a specific residential area in Kuwait with high traffic and industrial influences. Seven input variables, including four important meteorological parameters (wind speed, wind direction, relative humidity and solar radiation) and the ambient concentrations of three gaseous pollutants (methane, carbon monoxide and ozone) were fuzzified using a sytem with a graphical user interface (GUI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 58 publications
2
33
0
Order By: Relevance
“…Yetilmezsoy and Abdul-Wahab [88] utilized CH 4 , CO, wind speed and direction, relative humidity and solar radiation as the input variables of fuzzy and linear regression techniques for the estimation of PM 10 in Khaldiya, Kuwait. The fuzzy method outperformed the linear technique (MLR: R 2 = 0.756; Fuzzy technique: R 2 = 0.997).…”
Section: Other Techniquesmentioning
confidence: 99%
“…Yetilmezsoy and Abdul-Wahab [88] utilized CH 4 , CO, wind speed and direction, relative humidity and solar radiation as the input variables of fuzzy and linear regression techniques for the estimation of PM 10 in Khaldiya, Kuwait. The fuzzy method outperformed the linear technique (MLR: R 2 = 0.756; Fuzzy technique: R 2 = 0.997).…”
Section: Other Techniquesmentioning
confidence: 99%
“…Air quality is deteriorating in several developing countries (Naerher et al, 2000;Yetilmezsoy and Abdul-Wahab, 2012;Abdul-Wahab et al, 2015). According to the World Health Organization (WHO) report published in 2014 (WHO, 2014), many cities in developing countries are currently in breach of WHO guidelines on air pollution levels.…”
Section: Introductionmentioning
confidence: 99%
“…Other descriptive performance indices such as PSE and FV also revealed that the proposed empirical models gave very small residuals and demonstrated a noticeable estimation performance on forecasting of the studied the aeration-related parameters. Furthermore, the DW statistics (DWmodel-1 = 1.969, DWmodel-NEW EXPLICIT FORMULATIONS FOR ACCURATE ESTIMATION OF AERATION-RELATED PARAMETERS 155 2 = 1.892, and DWmodel-3 = 1.943) were determined to be very close to 2, indicating the goodness of fit of the derived models (Yetilmezsoy, 2016;Yetilmezsoy and Abdul-Wahab, 2012;Hewings et al, 2002).…”
Section: Measuring Of the Goodness Of The Estimatementioning
confidence: 99%
“…Moreover, the p-value is used as a useful tool to check the significance of each of the coefficients. The variable with the larger tratio and with the smaller p-value is considered as the more significant parameter in the regression model (Yetilmezsoy and Sapci-Zengin, 2009;Yetilmezsoy and Sakar, 2008;Yetilmezsoy and Abdul-Wahab, 2012). It is also noted that values that yield Prob(t) factors (or p-values) of greater than 0.9 may be neglected until all remaining factors are calculated at once (Fingas and Fieldhouse, 2009).…”
Section: Proposed Formulations and Estimation Of Sord Ec And Kladmentioning
confidence: 99%